2012
DOI: 10.1177/0004867412443900
|View full text |Cite
|
Sign up to set email alerts
|

The impact of alcohol and illicit drugs on people with psychosis: The second Australian national survey of psychosis

Abstract: The use of alcohol and illicit substances is common among people with a psychotic illness, with a concerning upward trend in rates of substance abuse/dependence since the 1997-1998 survey. Clinicians should be aware of the potential impact of concurrent substance use and provide integrated treatment for individuals presenting with psychotic illnesses. More research and investment in new intervention programs is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 28 publications
4
56
0
Order By: Relevance
“…11 Abuse of stimulants and other illicit drugs was also high, with over 70% of participants reporting lifetime use of these drugs. 31 Both acute use (such as mild intoxication whilst undertaking testing) and chronic abuse of alcohol and cannabis are associated with cognitive impairment, and again these factors may aggravate poor cognitive function in people with schizophrenia.…”
Section: Potential Confounds In Measuring Cognitive Deficits In Schizmentioning
confidence: 99%
“…11 Abuse of stimulants and other illicit drugs was also high, with over 70% of participants reporting lifetime use of these drugs. 31 Both acute use (such as mild intoxication whilst undertaking testing) and chronic abuse of alcohol and cannabis are associated with cognitive impairment, and again these factors may aggravate poor cognitive function in people with schizophrenia.…”
Section: Potential Confounds In Measuring Cognitive Deficits In Schizmentioning
confidence: 99%
“…The number of people who present to acute mental health services with co-occurring mental illness and drug and/or alcohol problems is increasing with an upward trend in rates of substance abuse/dependence noted between 1997-1998 (Kavanagh et al, 2004) and 2010 (Moore, Mancuso, Slade, Galletly, & Castle, 2012). Rates between 25 to 60% have been reported in other Australian studies (Hoolahan, Kelly, Stain, & Killen, 2006; Australian Bureau of Statistics, 2007) and in the United Kingdom (20-37%) and the United States of America (38-50%) (Carra & Johnson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We found that 51% of participants had a substance use disorder, including 29% with a cannabis disorder and 13.9% with a stimulant use disorder. By comparison, the Australian Survey of High Impact Psychosis (Moore et al, 2012b) found that 35% of people with schizophrenia spectrum disorders reported cannabis use at least monthly in the previous 12 months, and 13.8% reported stimulant use at least monthly. A more significant limitation in our study may be that the quality of diagnostic information in this study is systematically poorer in community data, where diagnoses are recorded by clinicians rather than extracted by coders.…”
Section: Advantages and Limitationsmentioning
confidence: 96%
“…It occurs in up to half of people with first episode psychosis (Wisdom et al, 2011;Green et al, 2005;Addington and Addington, 2007;Wade et al, 2005;Grech et al, 2005;Archie et al, 2007) and schizophrenia (Regier et al, 1990;Kavanagh et al, 2004;Moore et al, 2012b). People with psychosis use cannabis at least ten times more frequently than the general population of the same age (Green et al, 2005;Koskinen et al, 2010;Degenhardt and Hall, 2012b).…”
Section: Substance Comorbidity In Psychosismentioning
confidence: 99%
See 1 more Smart Citation